Design and implementation of elliptical mantle cloaks for polarization decoupling of two tightly spaced interleaved co-frequency patch array antennas - Reza Masoumi; Robab Kazemi; Aly E. Fathy (Scientific Reports, 2023)
Abstract In this paper, we utilized the method of mantle cloaking to decouple/isolate two densely packed interleaved patch array antennas operating at the same frequency but with orthogonal polarizations. To reduce mutual coupling between the adjacent elements, vertical strips, as a type of elliptical mantle cloaks, are located in close proximity to the patches. At the operating frequency of f 0 = 3.7 GHz, the edge-to-edge spacing of the elements of the two interleaved arrays is less than λ 0/80 (1 mm) and the center-to-center spacing of each array element is 0.7 λ 0 (57 mm). The proposed design is implemented using 3D printing technology, and its performance in terms of return loss, efficiency, gain, radiation patterns, and isolation is measured for evaluation. The results show the radiation characteristics of the arrays are perfectly retrieved after cloaking similar to the isolated arrays. Decoupling tightly spaced patch antenna arrays on a single substrate paves the way to achieve miniaturized communication systems with full duplex operation or dual polarization communication.